Campaña social requerida por EcoCiencia (ONG) para la concienciación sobre el desperdicio de agua potable en la ciudad de Quito - Borlandelli Ojeda, Pablo Agustín (2004)
The waste of drinking water is a fact in many places in the world. Undoubtedly, overusing this element represents a major problem that will be reflected in the future, when it is scarce worldwide. Water will not exist forever, and for the same reason we must preserve it. Below is the proposal of a social campaign, which aims to raise awareness among the population of the city of Quito about the consequences that can result from the waste of drinking water. It is a work done in conjunction with the EcoCiencia Ecological Studies Foundation, in support of its Environmental Education project: Water sources for Quito. The idea is to complement the activities of this Non-Governmental Organization, by proposing a social campaign, which is aimed exactly at the social group of the city that most requires it. In a nutshell, those who waste the most drinking water ... See attached file